Taxonomic composition, abundances, and biovolumes of prey organisms in in-situ grazing experiments with Eudiaptomus gracilis in Upper Lake Constance (Überlinger See) in autumn 1998 - Alessandra Janina Kunzmann; Harald Ehret; Elizabeth Yohannes; Dietmar Straile; Karl-Otto Rothhaupt (PANGAEA, 2019)
The dataset compiles cell counts and biovolumes of different plankton groups (phytoplankton, ciliates, rotifers, heterotrophic nanoflagellates, and bacteria) obtained from three in situ bottle experiments conducted in September/October 1998 with the copepod Eudiaptomus gracilis as grazer.
Supplement to: Kunzmann, AJ et al. (2019): Calanoid copepod grazing affects plankton size structure and composition in a deep, large lake. Journal of Plankton Research, 41(6), 955-966, https://doi.org/10.1093/plankt/fbz067